Designing for cohesive project implementations enhancing corporate & thematic identities - Santaromana, Francis L. (2005)
Buildings of integral development TALK, and are INTERACTIVE not only in function but by virtual images as well. It cannot be ignored that opportunities of impact exist and add value to the greater recall. These are not just limited to qualitative assessment but are quantifiable if appropriate tools and benchmarks are applied. A new language to justifiable creative investment is defined as well as a reference to INFORMED decision making.

1.0 The Parallelogram Design Process: A methodology that provides branches, extensions, and adjustments particular of cohesive projects applications and testing, parallel to both form & function development.
2.0 Cohesive Approach to As-built Identity:
2.1 Form Legibility: Factors on Mass, Color, Recall and Impact
2.2 Visual Identification: Effective Retention of Icons, Users, and Corporate Images
2.3 Effectivity of Design Styles: Aesthetics, Consistency, Intrigue, Mystery, and Abstract Nature
3.0 Impact Assessment Tools: Programs and methodologies to objectively measure effectivity of architectural applications.
3.1 Creative imageries: Interactive visuals & Photo Image Simulations
3.2 Measuring Site Values with points grading to predict maximum visual delivery.
4.0 Learnings from Recall and Recognition: A post-construction test and assessment for success and/or failure of application.
5.0 Summary of Objectives
5.1 Preserve and Enhance User Identity
5.2 Apply Parallel Approach to Basic Design Process
5.3 Assess and Measure Visual impact with As-built Environment.
5.4 Provide testing and visual control efficiencies
5.5 Ensure optimum results in visual deliverables
The benefits will yield qualitative and quantitative data for comparative evaluation of Design Visuals. It presents a planning tool that aims to provide a more efficient creative investment for the designers.

Lastly, it gives reference and justification to the less revealed design applications for use as information in clientele decision-making.